Serum inflammatory cytokines levels and the correlation analyses in Parkinson’s disease - Fu, Jiajia; Chen, Sihui; Liu, Jiao; Yang, Jing; Ou, Ruwei; Zhang, Lingyu; Chen, Xueping; Shang, Huifang (Frontiers in Cell and Developmental Biology, 2023)
Objective: To investigate the serum levels of inflammatory cytokines and the correlations with Parkinson's disease (PD) clinical symptoms. Methods: Serum levels of the cytokines, including IL-6, IL-8, and TNF--α, were measured in 273 PD patients and 91 healthy controls (HCs). The clinical manifestations of PD were assessed with nine different scales to evaluate the cognitive function, non-motor symptoms, motor symptoms and disease severity. The differences in these inflammatory indicators were examined between PD patients and HCs, and the correlations of these inflammatory indicators with clinical variables were analyzed in PD patients. Results: Serum levels of interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) in PD patients were higher than those in HCs, but serum interleukin-8 (IL-8) level was not significantly different from that in HCs. In PD patients, serum IL-6 level was positively correlated with age of onset, the Hamilton Depression Scale (HAMD), and the Non-Motor Symptom Scale (NMSS), UPDRS part I, part II, and part III, but it was inversely correlated with the Frontal Assessment Battery (FAB) and the Montreal Cognitive Assessment (MoCA) scores. Serum TNF-α level was positively correlated with age of onset and H&Y stage in PD patients (P = 0.037), but negatively correlated with FAB scores in PD patients (P = 0.010). However, no associations were found between all the clinical variables and the serum IL-8 level. The forward binary logistic regression model revealed that serum IL-6 level was associated with MoCA (P = 0.023) and UPDRS I scores (P = 0.023), but no associations was found with the remaining factors. Conclusion: Our results suggest increased serum levels of IL-6 and TNF-α in PD, we further found that IL-6 level was associated with non-motor symptoms and cognitive dysfunction, this finding suggests that IL-6 may play a role in the pathophysiology of non-motor symptoms in PD, and that there may be a link between periphery inflammatory processes and non-motor symptoms and cognitive impairment.